Modern Vectors of Russian Diplomacy in the Post-Soviet Space - O. G. Karpovich; A. V. Davydova (Проблемы постсоветского пространства)
The countries of the post-Soviet space are of particular importance for Russia’s geopolitical interests. This primarily concerns the political and economic processes taking place in them. Moreover, of great importance are the approaches of the post-Soviet countries to cooperation with Russia and integration processes in the post-Soviet space. In view of significant negative trends in the international arena, the consolidation of the post-Soviet space is acquiring paramount significance. Numerous challenges and complexity of the tasks that Russia is facing in the present region underscore the need for a balanced, pragmatic and forward-looking approach in bilateral and multilateral relations with the states. The focus of Russian diplomacy is still on Ukraine, the countries of the South Caucasus and Central Asia, Moldova and Belarus. These countries are the priority partners of Russia, the priority of its foreign policy.